The American friend - Highsmith, Patricia
Tom Ripley has a sweet deal with an art forger. The forger creates the paintings; Tom sells them. But another criminal business associate wants Tom to go in for an even riskier enterprise: murder. Tom suggests his associate ask a local picture framer instead. That man has a fatal disease, or so it's rumored. More, he has a wife and kid that surely he wouldn't want to leave penniless. Let this picture framer be a hit man, and no one will suspect. The terminally ill craftsman may agree to the misdeed, and several more, but he'll end up needing Tom Ripley in a pinch. Written by J. Spurlin